Role of enamel deminerlization and remineralization on microtensile bond strength of resin composite - Rizvi, Abbas; Zafar, Muhammad S.; Al-Wasifi, Yasser; Fareed, Wamiq; Khurshid, Zohaib (European Journal of Dentistry, 2016)
Objective: This study is aimed to establish the microtensile bond strength of enamel following exposure to an aerated drink at various time intervals with/without application of remineralization agent. In addition, degree of remineralization and demineralization of tooth enamel has been assessed using polarized light microscopy. Materials and Methods: Seventy extracted human incisors split into two halves were immersed in aerated beverage (cola drink) for 5 min and stored in saliva until the time of microtensile bond testing. Prepared specimens were divided randomly into two study groups; remineralizing group (n = 70): specimens were treated for remineralization using casein phosphopeptides and amorphous calcium phosphate (CPP-ACP) remineralization agent (Recaldent™; GC Europe) and control group (n = 70): no remineralization treatment; specimens were kept in artificial saliva. All specimens were tested for microtensile bond strength at regular intervals (1 h, 1 days, 2 days, 1 week, and 2 weeks) using a universal testing machine. The results statistically analyzed (P = 0.05) using two-way ANOVA test. Results: Results showed statistically significant increase in bond strength in CPP-ACP tested group (P < 0.05) at all-time intervals. The bond strength of remineralizing group samples at 2 days (~13.64 megapascals [MPa]) is comparable to that of control group after 1 week (~12.44 MPa). Conclusions: CPP-ACP treatment of teeth exposed to an aerated drink provided significant increase in bond strength at a shorter interval compared to teeth exposed to saliva alone.
Keywords: Aerated drinks; microtensile bond strength; remineralization-demineralization; remineralizing agent